Evaluation of the Clinical, Biochemical, Neurological, and Genetic Presentations of Glutaric Aciduria Type 1 in Patients From China - E., Huishu; Liang, Lili; Zhang, Huiwen; Qiu, Wenjuan; Ye, Jun; Xu, Feng; Gong, Zhuwen; Gu, Xuefan; Han, Lianshu (Frontiers in Genetics, 2021)
Purpose: To characterize the phenotypic and genotypic variations associated with Glutaric aciduria type 1(GA1) in Chinese patients. Methods: We analyzed the clinical, neuroradiological, biochemical and genetic information from 101 GA1 patients in mainland China. Results: 20 patients were diagnosed by newborn screening and the remaining 81 cases were identified following clinical intervention. Macrocephaly was the most common presentation, followed by movement disorders and seizures. 59 patients were evaluated by brain MRI and 58 patients presented with abnormalities, with widening of the sylvian fissures being the most common symptom. The concentration of glutarylcarnitine in the blood, glutarylcarnitine/capryloylcarnitine ratio, and urine levels of glutaric acid were increased in GA1 patients and were shown to decrease following intervention. 88 patient samples were available for genotyping and 74 variants within the GCDH gene, including 23 novel variants, were identified. The most common variant was c.1244-2A>C (18.4%) and there were no significant differences in the biochemical or clinical phenotypes described for patients with the four most common variants: c.1244-2A>C, c.1064G>A, c.533G>A, and c.1147C>T. Patients identified by newborn screening had better outcomes than clinical patients. Conclusions: Our findings expand the spectrum of phenotypes and genotypes for GA1 in Chinese populations and suggest that an expanded newborn screening program using tandem mass spectrometry may facilitate the early diagnosis and treatment of this disease, improving clinical outcomes for patients in China.